Strategi Pengembangan Sumber Daya Manusia pada CV. Bumi Desain Mandiri Sukabumi - Kharisma , Kharisma (JUDICIOUS, 2025)
This research aims to analyze the human resource (HR) development strategy at CV. Bumi Desain Mandiri, a company operating in the construction sector. The research method used is qualitative with a case study approach. Data was collected through in-depth interviews with management and employes, as well as participato obesrvation and analysis of company documents. The research result show that CV. Bumi Desain Mandiri implements various human resource development strategies, including employes training and development, performance appraisals, and employes benefits programs. We hope that these results can help other construction companies in developing their human resources.